(untitled) (Bangladesh Journal of Botany, 2015)
Orbilia curvatispora Bond., O. sarraziniana Bond. and O. xanthostigma (Fr) Fr. belonging to the family Orbiliaceae were recorded. Since, these three taxa we have been considered on new report to the Turkish mycobiota at family level. These species can be characterized by the presence of thin ascospores along with the small ascocarps. An identification key were also given in the text for the species. DOI: http://dx.doi.org/10.3329/bjb.v44i1.22729 Bangladesh J. Bot. 44(1): 91-95, 2015 (March)